Durability of Polymer Electrolyte Membrane Fuel Cells Operated at Subfreezing Temperatures. Issue 13 (1st January 2016) - Macauley, Natalia; Lujan, Roger W.; Spernjak, Dusan; Hussey, Daniel S.; Jacobson, David L.; More, Karren; Borup, Rodney L.; Mukundan, Rangachary
Abstract : The structure, composition, and interfaces of membrane electrode assemblies (MEA) and gas-diffusion layers (GDLs) have a significant effect on the performance of single-proton-exchange-membrane (PEM) fuel cells operated isothermally at subfreezing temperatures. During isothermal constant-current operation at subfreezing temperatures, water forming at the cathode initially hydrates the membrane, then forms ice in the catalyst layer and/or GDL. This ice formation results in a gradual decay in voltage. High-frequency resistance initially decreases due to an increase in membrane water content and then increases over time as the contact resistance increases. The water/ice holding capacity of a fuel cell decreases with decreasing subfreezing temperature (−10°C vs. −20°C vs. −30°C) and increasing current density (0.02 A cm −2 vs. 0.04 A cm −2 ). Ice formation monitored using in-situ high-resolution neutron radiography indicated that the ice was concentrated near the cathode catalyst layer at low operating temperatures (≈−20°C) and high current densities (0.04 A cm −2 ). Significant ice formation was also observed in the GDLs at higher subfreezing temperatures (≈−10°C) and lower current densities (0.02 A cm −2 ). These results are in good agreement with the long-term durability observations that show more severe degradation at lower temperatures (−20°C and −30°C).